A Case of Primary Lung Cancer Producing Alpha-Fetoprotein - Toshiyuki Yamagata; Yuko Yamagata; Masanori Nakanishi; Kazuto Matsunaga; Yoshiaki Minakata; Masakazu Ichinose (Canadian Respiratory Journal)
A case of lung carcinoid showing elevated plasma alpha-fetoprotein (AFP) level is reported. A 44-year-old man who complained of the development of bloody sputum had a left hilar lung mass on chest radiograph. The serum level of AFP was markedly increased to 8438 ng/mL. After resection, it was diagnosed as an atypical carcinoid, and the tumour cells were positive for cytoplasmic AFP. AFP is one of the most useful tumour markers for the diagnosis of hepatic cell carcinoma or germ cell tumours. It has also been reported that some primary lung tumours produce AFP. However, these tumours are mainly poorly differentiated adenocarcinomas or large cell carcinomas. A lung carcinoid that produces AFP is extremely rare.